The effect of self-talk in learning the volleyball service skill and self-efficacy improvement - Zetou, E.; Vernadakis, N.; Bebetsos, E.; Makraki, E. (Journal of Human Sport & Exercise, 2012)
In this study the effect of self-talk on learning the volleyball service skill was examined and also the self-efficacy improvement. Participants were 57 female players 13 years old (mean age =12.83, SD=0.97) with two years experience (M=1.99, SD=0.67). Prior to the beginning of the program, participants were randomly assigned into two groups: a. the instructional self-talk group (ISTG, n = 28) and b. the control (traditional) group (CG, n = 29). All athletes followed a four-week practice program, aiming at overhand service skill learning and self-efficacy improvement. The program consisted of two practice units (60 min) per week. Participants of ISTG were taught to use the self-talk (for technique) loud before they performed the service drills. The control group received traditional feedback, that is, knowledge of performance and knowledge of results provided by the instructor. Service performance was assessed by videotaped evaluations in five basic elements of skill. There were three measurement periods for field test: pre-, post- and retention tests (one week after post-test). ANOVA repeated measures revealed significant interaction between groups and measures. There was also significant interaction between groups and self-efficacy scores. The results indicated that participants of the ISTG had better scores in the final measurement than the control group, when technique was evaluated and improved also their self-efficacy. In conclusion the Self-talk helps female volleyball athletes to improve performance and learning of overhand service skill and to improve also their self-efficacy. This study adds some useful elements to practitioners and how they used self-talk in the practice.